Emotions and acceptance towards artificial intelligence and its evolution - Santos, Gabriela Morais dos (2019)
Artificial Intelligence (AI) is one of the ultimate riddles of today’s generations and its applications are increasing day by day. Without realising, we deal with AI in the subtlest ways. Its rapid development has triggered several opinions among scientists, such as Elon Musk and Stephen Hawking, due to the controversial consequences it may imply. Apart from experts’ opinions, everyone belonging in society will be affected, whether positively or negatively. The present study aims to understand what kind of emotions are triggered by AI evolution, and if those emotions play a moderator role on the effect of AI acceptance on the agreement on which AI should evolve or not, with or without regulators. We ran a mixed methodology through a sample of 205 participants, applying an online survey, where we assessed the participants’ emotions regarding AI stimuli across three times, and further conducting a semi-structured interview. We concluded that, as opposite to what literature states, negative emotions tend to rise as the contact and knowledge regarding AI deepens. Symmetrically, non-negative emotions tend to decrease. Negative emotions seem to function as a moderator on the relationship between variables mentioned above. Also, the participants’ vision towards AI evolution seems to be hopeful, yet they recognise the need for regulators to be imperative.